The Historical Development of Entrepreneurship from Ancient Times to The Digital Era - Farhana, Hana; Azzahra, Faiza Nafaki; Nisa, Nabilah Khoirun; Saputra, Dika; Nurhasanah, Fatiya Nur (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Entrepreneurship in the Islamic perspective is an integral part of an economic system Basid on the values of tawhid, justice, and balance between material and spiritual interests. The history of Islamic entrepreneurship shows the continuous development of the Muslim economic sphere from the prophetic era to the modern age. During the time of Prophet Muhammad (PBUH), entrepreneurial practices served as both a means of da’wah and an instrument for shaping business ethics that emphasized trustworthiness, honesty, and fairness in transactions. These values were later developed systematically during the era of the Rightly Guided Caliphs (Khulafaur Rasyidin) through the establishment of economic institutions such as the baitul mal and zakat policies that aimed at equitable distribution of welfare. Subsequently, during the Umayyad and Abbasid dynasties, Islamic entrepreneurship reached its peak, marked by the emergence of international trade centers, innovations in monetary systems, and the growth of transcontinental trading networks that positioned the Islamic world as a global economic hub.